Numerical Design of a 3-Stage Cascaded Thermal Energy Storage System for Solar Application - Oguike, Chimezie (Department of Mechanical Engineering, 2023)
The analysis of a three-stage cascaded thermal energy storage is presented in this dissertation. Cascaded thermal energy storage systems has many advantages over conventional thermal energy storages, majorly it allows for maintaining of a nigh-constant temperature between the HTF and PCM during the charging and discharging cycles leading to improved performance of the system. This dissertation investigates the performance and transient response of a packed bed operating under high-temperature conditions with phase change materials in varying encapsulations (cascaded in a three-stage format) during charging and discharging cycle by employing computational numerical techniques via commercially available ANSYS Fluent software. The analysis was performed for nine different encapsulation geometries with increased surface area and constant volume in comparison to the base geometry (sphere) to determine the effects of each new encapsulation on the performance of the thermal energy storage (TES). The computational model used in the development of this work compares well with the experimental results by Raul [1]. Additionally, the effect of packing scheme/PCM layout is also investigated in this work. Comparative data analysis was performed on the TES with the various PCM encapsulation designs and the standard spherical PCM encapsulation to determine which geometry provides better performance during charging and discharging cycles. The results of this study show that the thermal performance of the cascaded thermal energy storage improves with each new encapsulation as evidenced by the decreases in charging and discharging times in comparison to the base encapsulation. This study also highlights which capsule design is most practical when considering the bed dimension increases/ decreases with in increasing thermal performance. This study's findings can serve as a benchmark for future optimization of cascaded thermal energy storage systems.